Effects of cold environment exposure on female reproductive health and its regulatory mechanisms - Sun, Hongyi; Zhao, Qianqian; Liang, Xiaolan; He, Yalun; Li, Yangshuo; Yu, Jin; Ding, Jie; Yu, Chaoqin (Frontiers in Genetics, 2025)
ObjectiveTo investigate the effects of cold environment exposure on female reproductive capacity and explore its potential regulatory mechanisms.MethodsFemale mice were subjected to cold water immersion to simulate cold environment exposure. Weight changes during cold exposure were recorded. Serum levels of anti-Müllerian hormone (AMH), estradiol (E2), follicle-stimulating hormone (FSH), and luteinizing hormone (LH) were measured using enzyme-linked immunosorbent assay (ELISA). Ovarian and uterine tissues were collected via surgical procedures, and transcriptomic sequencing was performed to explore potential regulatory mechanisms. ELISA was used to assess the levels of inflammatory cytokines, including interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-18 (IL-18), and tumor necrosis factor-alpha (TNF-α) in peritoneal fluid. Furthermore, immunohistochemistry was used to detect the expression levels of IL-1, IL-6, and IL-18 in ovarian tissues, as well as IL-6 and IL-18 in uterine tissues.ResultsCompared with the control group, female mice exposed to cold environments exhibited a significant increase in body weight and elevated serum levels of AMH, E2, FSH, and LH. Transcriptomic sequencing of ovarian and uterine tissues indicated that differentially expressed genes were primarily enriched in inflammation-related pathways, including the cAMP signaling pathway, cytokine-cytokine receptor interaction, and PI3K-Akt signaling pathway. Additionally, levels of inflammatory cytokines in the peritoneal fluid, including IL-1β, IL-6, IL-18, and TNF-α, were significantly elevated. Immunohistochemical analysis showed that the expression levels of IL-1, IL-6, and IL-18 were markedly increased in ovarian tissue, while IL-6 and IL-18 expression levels were significantly elevated in uterine tissue. These differences were statistically significant (P < 0.05).ConclusionCold environment exposure may induce inflammatory responses in the uterus and ovaries, contributing to the formation of an inflammatory microenvironment in the reproductive system. This process may lead to disruptions in sex hormone levels and ultimately impair female reproductive capacity.